2018
DOI: 10.5664/jcsm.7544
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Well-Trained Ear: Incidental Detection of Catathrenia on Home Sleep Apnea Tests in Patients With Low Probability for Obstructive Sleep Apnea

Abstract: Catathrenia is a rare sleep-related breathing disorder marked by nocturnal groaning during prolonged exhalation. Home sleep apnea tests are growing in popularity, but no prior case reports exist documenting catathrenia detected by a home sleep apnea test. We report two cases of catathrenia incidentally detected in patients with low to intermediate risk of obstructive sleep apnea, in which diagnostic polysomnography was recommended but denied by insurers. Events were automatically scored as central apneas, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In literature, catathrenia has been described as a condition in serious diseases such as fatal insomnia [44], Pitt-Hopkins syndrome [52], or mental retardation [37]. In our analysis, we determined that the majority of the comorbidities was made up of general disorders, such as allergic rhinitis, depression, attention-deficit hyperactivity disorder (ADHD), or obesity [16,37,45]. Our review also determined that comorbidities (excluding sleep disorders) played a role in the presentation of groaning during the NREM sleep; they shortened the minimal and maximal episode duration and scored less points in ESS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In literature, catathrenia has been described as a condition in serious diseases such as fatal insomnia [44], Pitt-Hopkins syndrome [52], or mental retardation [37]. In our analysis, we determined that the majority of the comorbidities was made up of general disorders, such as allergic rhinitis, depression, attention-deficit hyperactivity disorder (ADHD), or obesity [16,37,45]. Our review also determined that comorbidities (excluding sleep disorders) played a role in the presentation of groaning during the NREM sleep; they shortened the minimal and maximal episode duration and scored less points in ESS.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one articles [16-19, 22, 25-28, 30-33, 37-54] were included for further analysis. These included 6 cohort studies [16,26,31,[42][43][44], 1 case-control study [39], 10 case series [19,22,24,25,37,38,40,41,45,47], and 14 case reports [17,18,27,28,30,32,33,46,[49][50][51][52][53][54]. However, in 3 studies [16,25,43], data was reported with SD and mean values.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have pointed out that groaning events, with a flat airflow signal similar to apneas, could be misclassified in home sleep apnea tests (HSAT) and PSG. 58 , 59 Therefore, catathrenia might be common in patients with OSA and has been underdiagnosed. These assumptions considering associations between catathrenia and OSA, need future investigations.…”
Section: Discussionmentioning
confidence: 99%